Alteration of inflammatory markers and adhesion molecules in women using oral contraceptives - Ozsurmeli, Mehmet; Bastu, Ercan; Comba, Cihan; Sucu, Mete; Arslan, Erol; Misirlioglu, Selahattin; Celik, Faruk; Zeybek, Sakir Umit; Buyukoren, Ahmet (CUKUROVA UNIV, FAC MEDICINE, 2019)
Purpose: The aim of the study is examine the effect of oral contraceptives on the serum levels of adhesion molecules and identify if the synthetic oestrogens provide protection against atherosclerosis. Materials and Methods: The interleukin 6 (IL-6), Tumor necrosis factor alfa (TNF Alfa), Vascular cell adhesion molecule 1 (VCAM-1), Intercellular Adhesion Molecule (ICAM-1), E selectin, P selectin, C selectin, C Reactive Protein (CRP) levels and erythrocyte sedimentation rate (ESH) of patients between 18-45, without additional illness, using oral contraceptives for contraception at least for three years were compared to healthy volunteers, aged between 18-45, having regular menstruation and without any additional diseases. Results: There has been no meaningful difference between the VCAM-1, ICAM-1, E selectin, P selectin, TNF alfa, IL 6, ESH levels of the two groups. Serum CRP levels are meaningfully higher in the group using oral contraceptives. Conclusion: Oral contraceptives change the serum levels of adhesion molecules. The change in the serum CRP levels might be due to the liver first pass effect.
Keywords: Oral contraceptives; intercellular adhesion molecule-1; mediators of inflammation